The Effect of Giving Lemon Aromatherapy to Reduce Nausea and Vomiting in Pregnant Women in the 1st Trimester in the Working Area of Sukaraja Tiga Health Center, East Lampung - Rosalia Pertiwi; Richta Puspita Haryanti; Amalia (PROFESSIONAL HEALTH JOURNAL, 2025)
Symptoms of nausea and vomiting during pregnancy, often referred to as "morningickness", are normal physiological reactions that occur in the first trimester of pregnancy. An increase in the hormones HCG and estrogen in the body triggers nausea and vomiting during pregnancy. This treatment is divided into two, namely the use of drugs in pharmacological therapy and the use of alternative ingredients such as lemon aromatherapy in non-pharmacological therapy. This study aims to identify the impact of lemon aromatherapy in reducing symptoms of nausea and vomiting in 1st trimester pregnant women in the Sukaraja Tiga Health Center, East Lampung. The quantitative research method used is quasi-experimental with a one group pre and post test approach. The number of pregnant women in the first trimester who will be studied in the period April to May 2024 is 27 people, whose gestational age ranges from 5 to 12 weeks, and experience symptoms of nausea and vomiting. The sampling method includes all samples selected deliberately using the purposive sampling method and tested using the paired sample T test. Through statistical analysis, the results of the T test were obtained with a p-value of 0.000, or p-value <0.05, indicating that lemon aromatherapy therapy had an effect on reducing nausea and vomiting in pregnant women in the first trimester in the Sukaraja Tiga Health Center, East Lampung Working Area. The hope is that pregnant women can feel better by using lemon aromatherapy to reduce nausea and vomiting.